A Digital Platform and Smartphone App to Increase Physical Activity in Patients With Type 2 Diabetes: Overview Of a Technical Solution (Preprint) - Stephanie E Bonn; Christina Alexandrou; Ylva Trolle Lagerros (2022)
UNSTRUCTURED Mobile Health (mHealth) solutions can be used to increase patients’ engagement in self-care. Descriptions of the technical solutions behind mHealth smartphone apps may guide the development of future apps. Here, we aim to describe the technical background and visual display of the DiaCert system, which was developed to support daily walking among patients with type 2 diabetes. The DiaCert system publishes one application program interface developed for patient devices (ie, smartphone apps running on iOS or Android) and another for web-based health care provider components (ie, administrative components). An individual care plan is created for each patient on the caregiver platform, and data on physical activity (ie, steps), blood samples, and questionnaires are shared between patient and caregiver in the DiaCert system. Technical solutions such as this enable us to reach more individuals at a lower cost compared to traditional health care. An advantage to the DiaCert technical solution is that it is built on a simple architecture and therefore is easily scalable. However, as it is a separate solution, it means adding yet another process for health care personnel to integrate into their work, which must be acknowledged. We hope that the technical description and visual display of the DiaCert system herein can guide researchers in the design and building of new and effective mHealth solutions. INTERNATIONAL REGISTERED REPORT RR2-10.1186/s12889-018-5026-4